A Systematic Review and Meta‐Analysis of the Efficacy of Cognitive Behavioral Therapy for the Management of Pediatric Migraine. Issue 3 (28th December 2016) - Ng, Qin Xiang; Venkatanarayanan, Nandini; Kumar, Lakshmi
Abstract : Introduction: Migraine headaches are common in children and adolescents. Current pharmacologic treatment options are limited despite the prevalence and debilitating effects of pediatric migraine. Cognitive behavioral therapy (CBT) is an evidence‐based practice that focuses on the development of coping strategies and cognitive restructuring to alter the pain experience. Till date, no meta‐analysis has been done to examine the use of CBT in pediatric migraine. Methods: Using the keywords (cognitive behavioral therapy OR cognitive behavior therapy OR cognitive behavioral therapy OR cognitive behavior therapy OR CBT) AND (headache OR migraine), a preliminary search on the PubMed and Ovid database yielded 3841 articles published in English between 1 Jan 1980 and 1 May 2016. Full articles were also reviewed for references of interest. After data extraction, 14 studies were included in the meta‐analysis. Results: The results of the meta‐analysis well‐support the clinical role of CBT in the management of pediatric migraine. The pooled odds ratios of clinically significant improvement, that is, 50% or greater headache activity reduction post‐treatment and at follow‐up (3 months or later) were OR 9.11 (95% CI: 5.01 to 16.58, P < .001) and OR 9.18 (95% CI: 5.69 to 14.81, P < .001) respectively, demonstrating significant clinical improvement with CBT as compared with wait‐list control, placebo, or standard medication. Furthermore, the clinical improvement was stable, even at a 1‐year follow‐up as evident in some of the studies. Conclusion: There is good evidence that CBT is beneficial to children suffering from migraine, and may also augment the efficacy of standard medications such as amitriptyline.